Women's Acts : Plays by Women Dramatists of Spain's Golden Age - Soufas, Teresa Scott (Book collections on Project MUSE., 2015)
Seventeenth-century Spain witnessed a rich flowering of dramatic activity that paralleled the Renaissance stage in other European countries. Yet this Golden Age traditionally has been represented in print almost entirely by male playwrights. With Women's Acts, Teresa Scott Soufas makes available eight plays by five long-neglected women dramatists: Angela de Azevedo, Ana Caro Mallen de Soto, Leonor de la Cueva y Silva, Feliciana Enriquez de Guzman, and Marla de Zayas y Sotomayor. In an age when moralists denounced women's participation in the public arena, these women transgressed traditional g.